Penerapan Pijat Refleksi Kaki terhadap Tekanan Darah pada Penderita Hipertensi - Damayanti, Nadia Tri; Sulistiowati, Sri (Neolectura, 2026)
Hypertension is influenced by various factors, including age, genetic history, a sedentary lifestyle, psychological stress, high-sodium diet, smoking, and lack of physical activity. Hypertension management includes pharmacological therapy with antihypertensive medications and non-pharmacological approaches such as relaxation techniques. Foot reflexology is one non-pharmacological intervention that can provide a relaxing effect, potentially lowering blood pressure in individuals with hypertension. The purpose of this study was to determine the application of foot reflexology to blood pressure in hypertensive patients. The method used was an observational case study, a research approach that aims to analyze or evaluate a physical object, process, or ongoing activity in two respondents. The results showed that foot reflexology was able to lower blood pressure in both respondents, with an average difference of 10 mmHg for the first respondent and 17.5-20 mmHg for the second respondent.